Implementasi Tata Naskah Dinas dalam Penciptaan Surat Keluar pada Dinas Pekerjaan Umum, Tata Ruang, Perumahan Rakyat dan Kawasan Permukiman dan Lingkungan Hidup Kabupaten Tasikmalaya - Anugrah, Satria Diatsa Putri; Aulianto, Dwi Ridho (Ilmu Informasi Perpustakaan dan Kearsipan, 2024)
Outgoing letters are a means of written communication between institutions that are used officially, and their implementation must be done using the service documents that apply within the organization. This research aims to determine the implementation of official scripts within the Department of Public Works, Spatial Planning, Public Housing and Settlement Areas, and the Environment of Tasikmalaya Regency. The descriptive-qualitative research method collects data through participant observation, interviews, and a literature study. The research results show that the level of suitability of official documents is quite good. This can be seen from various aspects analyzed, namely aspects of the structure of official letters, letter numbering, letter type and spacing, and the size of the paper used in making the letter. Habits, employee competence, and leadership commitment must be improved to implement official scripts. However, various efforts have been made to optimize the implementation of official document management through outreach activities, providing direction and consultation, compiling a summary of the official document management guidelines, and creating letter templates to create uniformity in preparing official letters.